Critical Fractional p-Laplacian System with Negative Exponents. (18th January 2023) - Zhu, Qinghao; Qi, Jianming
Abstract : In this paper, we consider a class of fractional p -Laplacian problems with critical and negative exponents. By decomposition of the Nehari manifold, the existence and multiplicity of nontrivial solutions for the above problems are established with respect to a sufficiently small parameter.